All Days 2001
DOI: 10.4043/13134-ms
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Foam Thermal Insulation for Ultra-Deepwater Oil and Gas Pipelines

Abstract: Syntactic foam has been used successfully for over thirty years in the offshore industry, primarily as a buoyancy material for supporting marine riser pipe, and in floats and buoys of various kinds. Now its use is growing as a thermal insulating material for subsea equipment and pipelines, ensuring continued flow of hydrocarbons under adverse conditions. Experience to date shows that syntactic foam can in many cases offer significant engineering and economic advantages compared to more conventional insulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In comparation, no other material can successfully provide both buoyancy and insulation in a compact, volumetrically-efficient package [20].…”
Section: Other Methods Used Thermal Insulationmentioning
confidence: 99%
“…In comparation, no other material can successfully provide both buoyancy and insulation in a compact, volumetrically-efficient package [20].…”
Section: Other Methods Used Thermal Insulationmentioning
confidence: 99%
“…High specific strength and low thermal conductivity are the major advantages of syntactic foams [1,2]. This composite has significant advantages such as high specific compressive strength, high damage tolerance, thermal and electrical insulation [3] and excellent damping properties [4]. One of the major advantages is its efficiency as a buoyancy material, which becomes a natural choice for insulating subsea equipment [3].…”
Section: Advantages Of Short Fibermentioning
confidence: 99%
“…These studies showed an improvement in mechanical properties with an increase in fiber volume fraction. From these studies [3][4][5] it is clear that the fiber length and fiber volume fraction are critical parameters in determining the properties of the composite. Zhu et al [8] proved that the reinforcement morphology had an effect on the mechanical properties of the short fiber composites.…”
Section: Advantages Of Short Fibermentioning
confidence: 99%
“…26 Initially this material was used for buoyancy for ultra-deep underwater exploration in the marine science domain in the 1970s. In this context, syntactic foams, which can be used alone or as the core of composite sandwich structures, are particularly attractive owing to their excellent specifi c properties, i.e.…”
Section: Case Study 3: Syntactic Foam For Deep Sea and Offshore Applimentioning
confidence: 99%